Compact Circularly Polarized Multiband Antennas for RFID Applications - H. M. El Misilmani; M. Al-Husseini; K. Y. Kabalan; A. El-Hajj (International Journal of Antennas and Propagation)
This paper presents multiband circularly polarized (CP) antennas for radio frequency identification (RFID). A coax-fed and a microstrip-line-fed antennas having optimized cross-slots in their patches are first designed for dual-band CP operation. The microstrip-line-fed design is then modified, by incorporating a U-shaped slot in its partial ground plane, to achieve additional operation band with a CP characteristic. Simulation and measured results of the presented designs are reported. The measured results are in accordance with the computed ones. The compact size and CP property make these designs suitable for RFID applications.